1973
DOI: 10.1002/1097-0142(197306)31:6<1392::aid-cncr2820310614>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of metastases formation by unspecific immunologic stimulation associated with heparintherapy

Abstract: The influence of unspecific (immunologic) stimulation of the reticulo‐endothelial system (RES) associated with an anticoagulant treatment (heparin) on metastasis formation has been studied in adult mice on which intravenous inoculation had been performed (tail vein) with 5 × 106/0.2 ml Ehrlich‐Lettré tetraploid ascites carcinoma cells. The mice were divided into four groups: I: controls; II. unspecifically stimulated RES; III. heparin treatment, and IV. stimulated RES (Polidin) plus heparin. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Our current findings are consistent with abundant in vitro and in vivo laboratory data, which suggest that anticoagulants, particularly LMWH, exert an antineoplastic effect 15–30, 50, 77. It has been reported that heparins inhibit primary tumor growth, reduce tumor cell motility, inhibit tumor cell migration, reduce the formation of metastases, enhance the antitumor effects of chemotherapy, and prolong the survival of laboratory animals after tumor cell inoculation 18, 24, 27, 31, 78–91.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our current findings are consistent with abundant in vitro and in vivo laboratory data, which suggest that anticoagulants, particularly LMWH, exert an antineoplastic effect 15–30, 50, 77. It has been reported that heparins inhibit primary tumor growth, reduce tumor cell motility, inhibit tumor cell migration, reduce the formation of metastases, enhance the antitumor effects of chemotherapy, and prolong the survival of laboratory animals after tumor cell inoculation 18, 24, 27, 31, 78–91.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with cancer frequently have laboratory evidence of hemostatic activation,7–10 and patients who are diagnosed with an idiopathic venous thrombosis are at increased risk of subsequently developing cancer 11–14. Considerable experimental data indicate that anticoagulants, in particular low‐molecular‐weight heparin (LMWH) and unfractionated heparin (UFH), exert an antitumor effect 15–32…”
mentioning
confidence: 99%
“…Heparin has been known for some years to have antitumor effects, 80 ascribed to nonspecific immune stimulation as well as the anticoagulant effect. 8081 Inhibition of thrombin may play a role, since this enzyme has mul-tiple biological effects, 82 although this has not always decreased metastasis in experimental models.…”
Section: Heparinmentioning
confidence: 99%
“…Prophylactic effects of BCG based on nonspecific stimulation of tumor defense have often been described [2,4,9,11]. Using i.v.…”
Section: Discussionmentioning
confidence: 99%